Mindfulness and athlete burnout among olympic combat sport athletes: the mediating role of athlete self-compassion and the moderating role of emotion regulation - Zülbiye Kaçay; Emrah Seçer; Özkan Işık; Yunus Şahinler; Laurentiu-Gabriel Talaghir; Mariana Constantinescu; Cristina-Corina Benţea; Teodora Mihaela Iconomescu (Frontiers in Psychology, 2026)
Introduction The present study aimed to examine the effect of sport mindfulness on athlete burnout among Olympic combat sport athletes and to investigate the mediating role of athlete self-compassion and the moderating role of emotion regulation in this relationship. Methods This study employed a cross-sectional correlational research design and included 379 athletes (279 men and 100 women) actively competing in Olympic combat sports. Data were collected using the Mindfulness Inventory for Sport, the Athlete Burnout Questionnaire, the Self-Compassion Scale–Athlete Version-Short Form and the Athlete Emotion Regulation Scale. The construct validity of the measurement instruments was evaluated using confirmatory factor analysis. Relationships among the study variables were examined using Pearson correlation analysis. The proposed hypotheses were tested using the PROCESS macro, specifically Models 4, 1, and 14. Results The findings indicated that sport mindfulness positively and significantly predicted athlete self-compassion (B = 0.155, p < 0.001). Athlete self-compassion, in turn, was found to have a significant negative effect on athlete burnout ( B = −0.798, p < 0.001). Furthermore, the interaction between athlete self-compassion and emotion regulation significantly predicted athlete burnout ( B = −0.060, p < 0.001). The moderated mediation analysis demonstrated that emotion regulation significantly moderated the indirect association between sport mindfulness and athlete burnout (Index = −0.009). Examination of the conditional indirect effects revealed that the burnout-reducing effect of sport mindfulness through athlete self-compassion was stronger among athletes with higher levels of emotion regulation. Conclusion The findings suggest that the association between sport mindfulness and athlete burnout cannot be explained solely by a direct relationship. Rather, this relationship operates through athlete self-compassion and varies according to athletes' levels of emotion regulation. These findings underscore the importance of integrating mindfulness-based skills, self-compassion development, and emotion regulation capacity into interventions designed to enhance psychological resilience and prevent burnout among combat sport athletes.